2002
DOI: 10.1590/s1679-87592002000100002
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in the spawning stock biomass and recruitment of the brazilian sardine (Sardinella brasiliensis) 1977-1997

Abstract: In the southeastern coast of Brazil, catches of the Brazilian sardine (Sardinella brasiliensis) have been decreasing from more than 200 thousand tons/year in the early '70s to about 32 thousand tons in 1990. From 1994 to 1997, catches recovered slightly (118 thousand tons), dropping then to about 20 thousand tons in 1999-2000. Extensive investigations on biology and stock assessment of Brazilian sardine have been developed in the '80s, providing stock biomass and recruitment estimates based on commercial fishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…The spawning habitat expansion and contraction pattern described above has been compared with independent estimates of the spawning stock biomass reported by Cergole (1995) and Cergole et al (2002) (Fig. 11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spawning habitat expansion and contraction pattern described above has been compared with independent estimates of the spawning stock biomass reported by Cergole (1995) and Cergole et al (2002) (Fig. 11).…”
Section: Discussionmentioning
confidence: 99%
“… Time series of spawning stock biomass (), recruitment () and yield () estimated by virtual population analysis for Sardinella brasiliensis (adapted from Cergole et al , 2002, with permission from the Brazilian Journal of Oceanography ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Southern Brazilian Continental Shelf (SBCS) is known as one of the more productive areas for fisheries in Brazilian waters [ Haimovici , ]. Many authors reported a strong relationship between the SBCS environmental variability and the Brazilian sardine ( Sardinella brasiliensis ) biological cycle and fisheries [ Matsuura , ; Sunyé and Servain , ; Cergole et al ., ; Legey and Jablonski , ; Gigliotti et al ., ; Soares et al ., ; Dias et al ., ; D'agostini et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The sardine S. brasiliensis occurs in tropical and subtropical waters of the western Atlantic and forms compact schools in coastal waters; these sardines are captured by local fisheries (Cergol et al, 2002). The family Engraulidae is the most abundant pelagic fish family in the south-western Atlantic.…”
Section: Stomach Contents and Isotopic Profiles Of Penguinsmentioning
confidence: 99%